A Self‐Supporting Strategy for Gas‐Phase and Slurry‐Phase Ethylene Polymerization using Late‐Transition‐Metal Catalysts. Issue 35 (22nd June 2020) - Dai, Shengyu; Chen, Changle
Abstract: The polyolefin industry is dominated by gas‐phase and slurry‐phase polymerization using heterogeneous catalysts. In contrast, academic research is focused on homogeneous systems, especially for late‐transition‐metal catalysts. The heterogenization of homogeneous catalysts is a general strategy to provide catalyst solutions for existing industrial polyolefin synthesis. Herein, we report an alternative, potentially general strategy for using homogeneous late‐transition‐metal catalysts in gas‐phase and slurry‐phase polymerization. In this self‐supporting strategy, catalysts with moderate chain‐walking capabilities produced porous polymer supports during gas‐phase ethylene polymerization. Chain walking, in which the metal center can move up and down the polymer chain during polymerization, ensures that the metal center can travel along the polymer chain to find suitable sites for ethylene enchainment. This strategy enables simple heterogenization of catalysts on solid supports for slurry‐phase polymerization. Most importantly, various branched ultra‐high‐molecular‐weight polyethylenes can be prepared under various polymerization conditions with proper catalyst selection. Abstract : Chain walking makes the difference : The utilization of chain‐walking features can enable new polymerization strategies (gas‐phase polymerization and heterogenized slurry‐phase polymerization) using existing late‐transition‐metal‐based olefin polymerization catalysts.